2022
DOI: 10.1016/j.molmet.2021.101404
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota-based vaccination engages innate immunity to improve blood glucose control in obese mice

Abstract: Objective Obesity and diabetes increase circulating levels of microbial components derived from the gut microbiota. Individual bacterial factors (i.e., postbiotics) can have opposing effects on blood glucose. Methods We tested the net effect of gut bacterial extracts on blood glucose in mice using a microbiota-based vaccination strategy. Results Male and female mice had improved glucose and insulin tolerance five weeks after a single subcutan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In contrast, other postbiotics such as under‐acylated LPS, NOD2 ligands, short chain fatty acids (SCFA), flavonoids, and flagellin have emerged as promotors of insulin sensitivity and glucose homeostasis (Anhê et al, 2021 ; Canfora et al, 2015 ; Cavallari et al, 2017 ; Cavallari et al, 2020 ; Kimura et al, 2013 ; Thaiss et al, 2016 ; Tran et al, 2019 ). Recent work showed that injection of crude extracts of intestinal luminal contents, containing a complex mixture of postbiotics, improves blood glucose control in HFD‐fed mice (Duggan et al, 2022 ; Pomié et al, 2016 ). The identity and interactions of the microbial factors responsible for glucose lowering remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other postbiotics such as under‐acylated LPS, NOD2 ligands, short chain fatty acids (SCFA), flavonoids, and flagellin have emerged as promotors of insulin sensitivity and glucose homeostasis (Anhê et al, 2021 ; Canfora et al, 2015 ; Cavallari et al, 2017 ; Cavallari et al, 2020 ; Kimura et al, 2013 ; Thaiss et al, 2016 ; Tran et al, 2019 ). Recent work showed that injection of crude extracts of intestinal luminal contents, containing a complex mixture of postbiotics, improves blood glucose control in HFD‐fed mice (Duggan et al, 2022 ; Pomié et al, 2016 ). The identity and interactions of the microbial factors responsible for glucose lowering remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Postbiotics include microbial components or metabolites that do not require detection of live bacteria to influence host immunity and metabolism (Cavallari et al, 2017 ; Cavallari et al, 2020 ; Cicenia et al, 2014 ; Patel & Denning, 2013 ). For example, microbial components sensed by pattern recognition receptors (PRRs) of the innate immune system can alter host metabolism (Canfora et al, 2015 ; Cani et al, 2007 ; Duggan et al, 2022 ; Perry et al, 2016 ; Tran et al, 2019 ; Turnbaugh et al, 2006 ). Specific postbiotics, such as bacterial cell wall‐derived muramyl dipeptide (MDP), have been shown to mitigate metabolic inflammation and improve aspects of metabolic disease during bacterial and nutritional stress (Canfora et al, 2015 ; Cavallari et al, 2017 ; Cavallari et al, 2020 ; Tran et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was possible that injection of specific doses of a gut bacterial extract derived from specific gastrointestinal tract segments could improve blood glucose control. After optimization of the dose and extraction, sonication, sterilization of postbiotic factors from the mucosa and lumen of the gut, several groups have shown that a single subcutaneous injection of a diluted bacterial extract from the upper gut caused long-term lowering of blood glucose a month later in lean mice [ 97 , 98 ]. This was one of the first bacterial immunization strategies that can improve blood glucose during obesity.…”
Section: Targeting the Microbiota To Improve Metabolism Through Nlrsmentioning
confidence: 99%
“…This was one of the first bacterial immunization strategies that can improve blood glucose during obesity. This immunization required bacteria, since mucosal extracts prepared from germ-free mice did not lower glucose [ 97 , 98 ]. Bacterial vaccination required NOD2 to lower blood glucose.…”
Section: Targeting the Microbiota To Improve Metabolism Through Nlrsmentioning
confidence: 99%
See 1 more Smart Citation